Hybridization of battery with pico hydel for frequency regulation of microgrids using synchronverter control - Vasudevan K.R.; Ramachandaramurthy V.K.; Venugopal G.; Guerrero J.M. (John Wiley and Sons Inc, 2023)
Agricultural robots; Eigenvalues and eigenfunctions; Electric batteries; Microgrids; System stability; Autonomous microgrids; Energy-capacity; Frequency nadirs; Frequency regulations; Hybridisation; Microgrid; Pico-hydel; Rate of change of frequencies; Renewable power generation; Storage systems; Energy storage